Combination of Open Subtotal Calcanectomy and Stabilization With External Fixation as Limb Salvage Procedure in Hindfoot-Infected Diabetic Foot Ulcers. (December 2016) - Dalla Paola, Luca; Carone, Anna; Boscarino, Giulio; Scavone, Giuseppe; Vasilache, Lucian
Diabetic hindfoot ulcers, complicated by osteomyelitis, are associated with a high risk of major amputation. Partial calcanectomy, preceded by an effective management of the infection and of the eventual peripheral artery disease, can be considered as valid therapeutic option. We have evaluated a therapeutic protocol for diabetic hindfoot ulcers complicated by osteomyelitis, which, besides an adequate surgical debridement, considers a reconstructive pathway assisted by the positioning of a circular external fixator. We made a prospective study of a cohort of diabetic patients affected by heel ulcer complicated by osteomyelitis. All patients underwent open partial calcanectomy associated with the positioning of a circular external frame specifically designed for hindfoot stabilization and offloading. A reconstructive procedure was implemented starting with the application of negative pressure wound therapy and coverage with dermal substitute and split thickness skin grafting. From November 2014 to November 2015, 18 consecutive patients were enrolled. Mean follow-up period was 212.3 ± 64.0 days. Healing was achieved in 18 (100%) patients. The mean healing time was 69.0 ± 64.0 days. No major amputation had to be performed during the follow-up. Open partial calcanectomy associated with external fixation and skin reconstruction was as efficient as limb salvage in patients with infected lesions of the hindfoot complicated by calcaneal osteomyelitis.